Kajian Penerapan Konsep Green City di Kelurahan Sekayu, Kota Semarang - Diah Septiorini; Andarina Aji Pamurti (Universitas Islam Raden Rahmat, Malang, 2023)
Global warming caused by trade and service activities and population density is a critical issue in the development of a city. The impact of global warming is climate change, increased air pollution, and decreased environmental quality. Sekayu Village is the central area of ​​Semarang city which has high economic activity. Sustainable cities can use the Green City concept. The purpose of this study was to identify the application of the Green City concept to Sekayu Village. The method used is descriptive quantitative. The results of the study are Green Planning and Design with basic building coefficients not all in accordance with the provisions, Green Open Space is an adequate green open space area, Green Waste does not have 3R waste management but has bank waste, Green Transportation is served by BRT public transportation, Green Water the environment has no water management, Green Energy low use of renewable energy, Green Buildings less use of environmentally friendly materials, Green Community there is no green community. With the scoring analysis technique, the level of application of the green city concept in Sekayu Village is in the low category.